Impact of climate change on pines forest productivity and on the shift of a bioclimatic limit in Mediterranean area - Vennetier M.; Vilà B.; Liang E.; Guibal F.; Taahbet A.; Gadbin-Henry C. (Proceedings of the international workshop MEDPINE 3: conservation, regeneration and restoration of Mediterranean pines and their ecosystems, 2007)
The experimental design includes a series of plots distributed along an altitudinal transect on the North slope of Sainte-Baume mountain. The choice of the site, homogeneous for rainfall regime, as well as the homogeneity in substrata, soil and topography at the level of plots, allows to focus on the variations of the response of trees due to differences in mean annual temperatures. Additional plots with soils much deeper or much shallower than those of the main transect also allow studying the interaction between climate and soil water balance on the growth of trees. The impact of the exceptional scorching heat and drought of year 2003 is also analyzed. The response of trees to monthly climatic parameters depends a lot on the annual mean temperature and soil water balance. The climate warming should thus produce significant effects on the short-term on forest productivity. While the productivity of the Pinus halepensis strongly increased during the 20th century, that of Pinus silvestris decreased strongly in the same period. Year 2003 reduced directly the growth of these pines. But, especially by its detrimental delayed effects on their health status and their leaf area, it limits their potential growth for several following years. The productivity of these two pines should be reduced strongly in the next decades. Many withering stands observed in Pinus silvestris distribution area since 2003 show that the survival of large areas of this species is threatened in the short or middle term by climate warming in the French Mediterranean region.
Proceedings of the International Workshop, 2005/09/26-30, Bari (Italy)